Circular Economy: Problems and Solutions at the Present Stage - A. P. Epishov; S. E. Zhura; S. V. Zavyalov; M. A. Kovalenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
Russia's transition to a circular economy requires the solution of a number of important problems which include various aspects of activity. The process of transition to sustainable economic development began at the end of the 20th century. This transition was enshrined in a number of legal acts of both international and domestic levels. Despite the widespread use of the term "circular economy" there is still no officially approved formulation of this concept. This makes it difficult to form quantitative indicators of achieving the set goals for the transition to this type of economy. The process of creating a fair mechanism for financing the waste management system in the country is hindered by artificial barriers in the form of administration, insufficiently substantiated environmental fee rates and recycling standards. The issue related to classifying waste as secondary material resources has not yet been worked out which requires amendments to the current legislation. There are no reliable data on the amount of waste generated and the degree of their impact on the environment and human health. We are required to form a unified information system containing data on the sources of waste generation. The solution of these problems, according to the authors of the study, will help improve the environment and human health.